1982
DOI: 10.1002/ajmg.1320110109
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis in 3,000 women for chromosome, X‐linked, and metabolic disorders

Abstract: In 3,000 women referred for prenatal diagnosis, 110(3.7%) abnormal fetuses were detected and 85 therapeutic terminations were performed. These were five main reasons for referral. Among the 2,227 women referred because of maternal age 35 years and older, there were 51 (2.3%) who had aneuploid fetuses. In the 297 women referred because of a previous child with Down syndrome, 3 aneuploid fetuses (1.0%) were detected. Of the 55 couples where one spouse was a carrier of a balanced chromosome rearrangement, 6 chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
4

Year Published

1983
1983
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
0
14
2
4
Order By: Relevance
“…En effet, dans les 14 études qui ont été utilisées pour fin de comparaison des motifs d'amniocentèse, 6 seulement présentaient des résultats globaux (Simpsons et al 1976;Henry et al 1978;Hsu et al 1978;Golbus et al 1979;Daniel et al 1982;Schmid 1990). Les autres auteurs s'attardaient plus spécifiquement aux anomalies chromosomiques trouvées dans les cellules amniotiques de patientes ayant consulté pour âge maternel avancé (Crandall et al 1980;Bartsch et al 1976;Dacus et al 1985).…”
Section: Résultatsunclassified
See 3 more Smart Citations
“…En effet, dans les 14 études qui ont été utilisées pour fin de comparaison des motifs d'amniocentèse, 6 seulement présentaient des résultats globaux (Simpsons et al 1976;Henry et al 1978;Hsu et al 1978;Golbus et al 1979;Daniel et al 1982;Schmid 1990). Les autres auteurs s'attardaient plus spécifiquement aux anomalies chromosomiques trouvées dans les cellules amniotiques de patientes ayant consulté pour âge maternel avancé (Crandall et al 1980;Bartsch et al 1976;Dacus et al 1985).…”
Section: Résultatsunclassified
“…La fréquence des résultats anormaux trouvés dans les anomalies chromosomiques sont semblables dans les 7 études, alors que celle des résultats anormaux pour âge maternel avancé est plus petite dans l'étude de Chicoutimi (1,3%) que dans celle de Golbus et al (1979) (3,5%), Daniel et al (1982) (2,2%), Schmid (1990) (1,9%), Simpsons et al (1976) (3,8%), Henry et al (1978) (1,9%), Hsu et al (1978) (4,6%). Cette différence pourrait être le résultat de population de taille différente dans les différentes études ou finalement de population à risque différent.…”
Section: Résultatsunclassified
See 2 more Smart Citations
“…2 However, there has been a number of families described with multiple trisomy 21 conceptions. [3][4][5][6][7][8][9][10] It has been suggested that in some families with multiple trisomy 21 conceptions, a genetic predisposition to nondisjunction of chromosome 21 may have been unmasked.…”
Section: Introductionmentioning
confidence: 99%